A stolen child - Taylor, Sarah Stewart (Taylor, Sarah Stewart. Maggie D'arcy mystery, 2023)
"After months of training, former Long Island homicide detective Maggie D'arcy is now officially a Garda. She's finally settling into life in Ireland and so is her teenage daughter, Lilly. Maggie may not be a detective yet, but she's happy with her community policing assignment in Dublin's Portobello neighborhood. When she and her partner find former model and reality tv star Jade Elliot murdered--days after responding to a possible domestic violence disturbance at her apartment--they also discover Jade's toddler daughter missing. Shorthanded thanks to an investigation into a gangland murder in the neighborhood, Maggie's friend, Detective Inspector Roly Byrne, brings her onto his team to help find the missing child. But when a key discovery is made, the case only becomes more confusing--and more dangerous. Amidst a nationwide manhunt, Maggie and her colleagues must look deep into Jade's life--both personal and professional--to find a ruthless killer"--